Aspectos relevantes da decisão proferida no processo administrativo tributário federal - Toccheto, Eliane Pereira Santos (2007)
The aim of this dissertation is to analyze the relevant aspects related to the decision on administrative proceeding concerning federal tax credits. Taking into consideration that the Constitutional principles are applicable to the tax administrative proceeding, such principles, as well as the federal legal tax system, are studied so as to present an overview of the tax administrative proceeding and to point out its peculiarities. Therefore, the questions related to the assessment of taxes and the federal tax proceeding's postulates are examined under the rules foreseen in Decree 70,235/72 and Law 9,784/99, as well as under the Acts issued by Brazilian Internal Revenue Service, General Attorney Office and Federal Treasury Ministry. As a result, the aspects of the decision rendered in the federal tax administrative proceeding, the appeals provided by law and also other means of revision of the final administrative decision are studied. Finally, the conclusions achieved by means of all the research and investigation referred above are briefly presented